Consequences of Jet-Ejecta Interaction in Neutron Star Mergers. Issue Volume 16:Issue S363(2020) (June 2020) - Nativi, Lorenzo; Rosswog, Stephan; Bulla, Mattia; Lundman, Christoffer; Lamb, Gavin P.; Kowal, Grzegorz
Abstract: In the first observed neutron star merger, GW170817, two dynamical components, mildly- and ultra-relativistic outflows were detected independently. The first component triggered a rapidly evolving thermal transient named macronova (kilonova), while the second caused an observed short GRB where the early gamma-ray signal was followed by a multi-wavelength afterglow. These two distinct components are typically modelled independently and the observational consequences of their interplay are hardly explored. Here we summarize the results of 3D special-relativistic simulations that we have used to investigate the consequences of jet propagation through a realistic environment. We show how the presence of a jet can lead to the macronova being brighter and bluer for on-axis observers in the first few days. Then we show the consequences on the interaction on the shape of the emerging jet. Finally, we will discuss how small scale features in the emerging jet structure can impact the best-fit afterglow parameters.